The History of The Emergence of The Arabic Language and Its Development: A Historical Analytical Study - Afril, Rezkya; Ansyah, Yogi Hajri; Satriyanto, Satriyanto (Universitas Al-Amien Prenduan, 2025)
This study presents a comprehensive historical-analytical review of the emergence and development of the Arabic language. Its aim to investigates the historical emergence and development of the Arabic language by systematically reviewing primary philological sources and secondary literature using a library research method within an analytical historical framework. It traces the position of Arabic within the Semitic language family, outlines the early phases of its development in the pre-Islamic period, and investigates the impact of the revelation of the Quran on the standardization and codification of the language. Building on this historical trajectory, the analysis shows that the expansion of the Islamic empire broadened the functions of Arabic, transforming it into a medium of administration, scholarship, and culture enriched through contact with diverse civilizations. Employing a library research method, the study qualitatively analyzes philological sources, the study highlights the period of stagnation following the fall of Baghdad and the subsequent revival during the Nahdah era, marked by lexical renewal and the revitalization of linguistic institutions. The findings indicate that the development of Arabic has not proceeded in a linear manner, but through recurring patterns of adaptation shaped by social, political, religious, and intellectual factors. Overall, this study emphasizes the resilience of the Arabic language and underscores its continued relevance in navigating modern sociocultural dynamics.